Rekonstruksi tari Penasar, wijil, dan Topeng Tua dalam Dramatari Topeng Panca di Desa Adat Batur Kintamani, Bangli - Suanditha, Kadek Rai; Suteja, I Ketut; Negara, I Gede Oka Surya (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2024)
Topeng Panca is a traditional dance form, and it is one of the mask performances performed by five dancers, each assuming different characters or roles: Topeng Keras, Topeng Tua, Topeng Dalem Arsa Wijaya, Topeng Penasar, and Topeng Sidakarya. The village of Batur was chosen as the partner by the author for the Merda Belajar – Kampus Merdeka (MBKM) program, specifically the Thematic Community Service Learning (KKNT). The reconstruction process of the Topeng Panca dance in the Batur village employed the Demonstration learning method, which involves presenting the material through demonstration or using movement media, making it easier for students to comprehend the presented content. The author's hope in reconstructing the Topeng Panca dance is to revitalize the art of Topeng dance, particularly in the endangered context of the Adat Batur village. In the future, during ceremonial events like odalan or Yandya ceremonies in the Batur village, the dancers can perform the Topeng Panca dance to enhance the flow of the Yandya ceremony in the village.